2016
DOI: 10.1016/j.ijmedinf.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and rehabilitation delivered through exergames in older adults: An integrative review of technologies, safety and efficacy

Abstract: Background: There has been a rapid increase in research on the use of virtual reality (VR) and gaming technology as a complementary tool in exercise and rehabilitation in the elderly population. Although a few recent studies have evaluated their efficacy, there is currently no in-depth description and discussion of different game technologies, physical functions targeted, and safety issues related to older adults playing exergames. Objectives: This integrative review provides an overview of the technologies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
202
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(235 citation statements)
references
References 84 publications
4
202
1
10
Order By: Relevance
“…For a number of years, the possibility of applying serious games for rehabilitation purposes has been thoroughly investigated [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. It is often claimed that serious games reduce health system costs and efforts as they enable in-home rehabilitation without loss of medical monitoring, and in so doing provide an additional fun factor for patients [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a number of years, the possibility of applying serious games for rehabilitation purposes has been thoroughly investigated [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. It is often claimed that serious games reduce health system costs and efforts as they enable in-home rehabilitation without loss of medical monitoring, and in so doing provide an additional fun factor for patients [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It is often claimed that serious games reduce health system costs and efforts as they enable in-home rehabilitation without loss of medical monitoring, and in so doing provide an additional fun factor for patients [22,23,24]. Multiple reviews have summarized the very powerful contributions and reveal that the systems are generally evaluated as feasible, but no state of general applicability has yet been reached [2,3,5,7,11,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Originating between the years 2000 and 2005, exergaming is defined as playing interactive video games using physical exertion as a form of exercise: exer (cise) plus gaming (Dictionary.com, 2016;Nawaz et al, 2015). Health professionals have explored the role of gaming technology to improve physical function in older adults; however, the evidence to support the effectiveness of using video games to encourage physical performance, also called exergames, would benefit from further studies to provide stronger scientific evidence (Molina, Ricci, de Morales, & Perracini 2014;Skjaeret, et al, 2015). For the purposes of this study, the term interactive video games (IVGs), also known as exergaming, will be used for consistency and clarity .…”
mentioning
confidence: 99%
“…Studies have found that further research is necessary to determine if the games are safe and which technology are most effective in improving physical functioning in older adults (Molina et al, 2014;Skjaeret et al, 2015). Most longitudinal studies with older adults have used Nintendo Wii platforms and off-the-shelf IVGs, which are popular among younger groups of gamers .…”
mentioning
confidence: 99%
See 1 more Smart Citation